Sibling Relations in Patchwork Families: Co-residence Is More Influential Than Genetic Relatedness - Gyuris, Petra; Kozma, Luca; Kisander, Zsolt; Láng, András; Ferencz, Tas; Kocsor, Ferenc (Frontiers in Psychology, 2020)
In “patchwork” families full siblings, maternal and paternal half-siblings and non-related children are raised together, and sometimes genetically related children are separated. As their number is steadily growing, the investigation of the factors that influence within-family relations is becoming more important. Our aim was to explore whether people differentiate between half- and full-siblings in their social relations as implied by the theory of inclusive fitness, and to test whether co-residence or genetic relatedness improves sibling relations to a larger extent. We administered the Sibling Relationship Questionnaire (SRQ) to 196 individuals who were in contact with full-, half-, or step-siblings in their childhood. We built GLMM models to test for the effects of relatedness and co-residence on sibling relations. In general, a higher degree of relatedness was associated with better sibling relations, but only among those who did not live together during childhood. Co-resident siblings’ overall pattern of relation quality was not influenced by the actual level of genetic relatedness. In contrast to this, full siblings reported having experienced more conflicts during childhood than half-siblings, possibly resulting from enhanced competition for the same parental resources. The results suggest that inclusive fitness drives siblings' relations even in recent industrial societies. However, among individuals who live together, the effect of relatedness might be obscured by fitness interdependence, and the subjective feeling of kinship.